ANALISIS ZONA BAHAYA GEMPABUMI BERDASARKAN METODE DETERMINISTIK DAN PENDEKATAN GEOMORFOLOGI KOTA PADANG SUMATERA BARAT - Azis Riyanti; Syamsurijal Rasimeng (Engineering Faculty Universitas Lampung, 2019)
Research on earthquake hazard analysis based on deterministic methods and the geomorphology approach of Padang City has been carried out to determine the maximum soil acceleration (PGA) and amplification of the source of the Suliti faults and Earthquake Subduction and determine soil classes based on shear waves (Vs30). The PGA value, several attenuation equations are used to find the magnitude of the shock produced when a shallow earthquake occurs. For the source of fault earthquakes, the attenuation equations used are the equivalent of Boore-Atkinson, Campbell-Bozorgnia, and Chiou-Young. While the attenuation equations used to obtain PGA values from subduction earthquake sources are Atkinson-Boore, Youngs, and Zhao. PGA value of earthquake source Subduction in bedrock 0.0374 g. While the PGA value on the surface is 0.0769 g. Whereas the PGA value in the fault source (Hard Fault) in bedrock ranged from 0.0376 g, while the PGA value on the surface ranged from 0.0573 g. Areas that have a severe impact if an earthquake originates from a fault are Koto Tengah District, West Padang Subdistrict, and North Padang Subdistrict with the highest amplification value of 1.7690 ( 9 times) which indicates that the magnification of the area is high. Whereas in the case of an earthquake with an earthquake source subduction area which is very vulnerable is West Padang District, Koto Tengah District, Padang Utara District with an amplification value of 2.0607 ( 9 times).